TMEM219 regulates the transcription factor expression and proliferation of beta cells - D’Addio, Francesca; Assi, Emma; Maestroni, Anna; Rossi, Giada; Usuelli, Vera; Petrazzuolo, Adriana; Nardini, Marta; Loretelli, Cristian; Ben Nasr, Moufida; Fiorina, Paolo (Frontiers in Endocrinology, 2024)
Pancreatic beta cells replenishment is considered the next therapeutic option for type 1 diabetes; while stimulating endogenous beta cells proliferation is the "holy grail" for those patients with exhausted beta cell mass. Here we are demonstrating that the pro-apoptotic receptor TMEM219 is expressed in fetal pancreas, in beta cell precursors and in in vitro embryonic-derived endocrine progenitors. TMEM219 signaling negatively regulates beta cells at early stages and induces Caspase 8-mediated cell death. Pharmacological blockade of TMEM219 further rescued beta cell precursor and proliferation markers, and decreased cell death, both in islets and in in vitro-derived endocrine progenitors, allowing for beta cell preservation. While addressing the upstream controlling TMEM219 expression, we determined the TMEM219 miRNet; indeed, one of those miRNAs, miR-129-2, is highly expressed in human islets, particularly in patients at risk or with established type 1 diabetes. miR-129-2 mimic downregulated TMEM219 expression in islets, in in vitro embryonicderived endocrine progenitors and in highly proliferating insulinoma-derived cells.Moreover, miR-129-2 inhibitor induced a TMEM219 overexpression in insulinomaderived cells, which restored cell proliferation and functional markers, thus acting as endogenous regulator of TMEM219 expression. The TMEM219 upstream regulator miR129-2 controls the fate of beta cell precursors and may unleash their regenerative potentials to replenish beta cells in type 1 diabetes.